Investigation of the Success Level of Namik Kemal Square as a Public Open Space - Moallem, Shirin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Nowadays one of the most important features of urban life is complication. Some of them were formed in work environment and activities, but concept of most of them was formed in social interaction. Hence, urban space plays an important role in social development of citizens. Social interaction are formed in these places. Therefore, lack of suitable urban space can create social abnormalities in cities. Square is one of the most significant factor, which can be formed social life in the past. There are several of locations in each urban square, which is creating motivate and attractiveness for users. For example, café, waterfront, sculpture, even an event that happened in the square. In fact, some of best urban square have different small attractiveness that improve the quality of square during the day. According the focus of this research the aim is to test the level of success of Namik Kemal square in the Walled City of Famagusta and to make proposals to turn it to make a successful public square. Namik Kemal square is a historic square, which is located in the Walled City of Famagusta. Famagusta is one of the main cities in North of Cyprus with lack of successful urban public open spaces. Main research question of this study is “what’s the level of successful in Namik Kemal square as an important historic public space in Famagusta?” for answering this question ,the research involves both qualitative research methods including literature survey, site analysis and observation and quantitative that including questioner. Keywords: Public Place, Public Open Space, Square, Namik Kemal Square ………………………………………………………………………………………………………………………… ÖZ: Günümüzde kentsel yaşamın en önemli özelliklerinden biri komplikasyonudur. wsosyal etkileşimde kurulmuştur. Bu nedenle, kentsel mekan vatandaşların sosyal gelişiminde önemli bir rol oynar. Sosyal etkileşimler bu yerlerde oluşturulur. Bu nedenle, uygun kentsel mekanın eksikliği şehirlerde sosyal anormallikleri oluşturabilir. Meydan geçmişte sosyal yaşamı oluşturan en önemli faktörlerden biridir. Kullanıcılar için motivasyon ve çekicilik oluşturmak için, her kent meydanında çeşitli yerler vardır. Örneğin kafe, rıhtımlar, heykel, hatta meydanda oldan bir olay. Aslında, en iyi kentsel meydanların bazısı gün boyunca meydanın kalitesini artırmak için farklı küçük etkinliklere sahiptir. Bu araştırmaya göre, amaç Mağusa Suriçinde Namık Kemal Meydanının başarı seviyesini test etmek ve başarılı bir kamu meydanına çevirmek önerilerde bulunmaktır. Mağusa Suriçinde bulunan Namık Kemal meydanı tarihi bir meydandır. Mağusa, başarılı kentsel kamusal açık alanların eksikliği ile Kuzey Kıbrıs'ın önemli şehirlerinden biridir. Bu çalışmanın temel araştırma sorusu "Mağusa'da önemli bir tarihi kamusal alan olarak Namık Kemal meydanında başarılı düzeyi nedir?" dir. Bu soruyu cevaplamak için, bu araştırma hem nitel araştırma yöntemleri; literatür taraması, site analizi ve gözlem dahil ve hem araştırma anketi içeren, nicel araştırma yöntemlerini içerir. Anahtar Kelimeler: Kamusal Yer, Kamusal Açık Alan, Meydan, Namık Kemal Meydanı.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Prof. Dr. Şebnem Önal Hoşkara.
Keywords: Architecture; Urban Design; City planning - Open Spaces - Public spaces - Famagusta (Cyprus, North); Urban landscape architecture - Famagusta (Cyprus, North); Public Place, Public Open Space, Square, Namik Kemal Square